The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1002/btm2.10562
|View full text |Cite
|
Sign up to set email alerts
|

Dual gene‐activated dermal scaffolds regulate angiogenesis and wound healing by mediating the coexpression of VEGF and angiopoietin‐1

Tingting Weng,
Min Yang,
Wei Zhang
et al.

Abstract: The vascularization of dermal substitutes is a key challenge in efforts to heal deep skin defects. In this study, dual gene‐activated dermal scaffolds (DGADSs‐1) were fabricated by loading nanocomposite particles of polyethylenimine (PEI)/multiple plasmid DNAs (pDNAs) encoding vascular endothelial growth factor and angiopoietin‐1 at a ratio of 1:1. In a similar manner, DGADSs‐2 were loaded with a chimeric plasmid encoding both VEGF and Ang‐1. In vitro studies showed that both types of DGADSs released PEI/pDNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 52 publications
(97 reference statements)
0
4
0
Order By: Relevance
“… 152 , 153 One study demonstrated increased angiogenesis in a rat full‐thickness wound model treated with gene‐activated dermal scaffolds loaded with PEI/plasmid DNAs encoding VEGF and angiopoietin‐1, compared to scaffolds loaded with plasmid VEGF alone or with the plasmid VEGF/angiopoietin‐1 chimeric plasmid alone. 130 In another study, Wang et al concluded accelerated wound healing, as evidenced by increased angiogenesis and decreased inflammation, in a splinted excisional burn wound model, when the wound was treated with a hydrogel scaffold loaded with resveratrol and PEI/plasmid DNA encoding VEGF (Figure 5a,b ). 125 Despite these promising features, the high cationic charge density of PEI can result in cytotoxicity that originates from cell membrane disruption through electrostatic interactions.…”
Section: Gf Gene Deliverymentioning
confidence: 95%
“… 152 , 153 One study demonstrated increased angiogenesis in a rat full‐thickness wound model treated with gene‐activated dermal scaffolds loaded with PEI/plasmid DNAs encoding VEGF and angiopoietin‐1, compared to scaffolds loaded with plasmid VEGF alone or with the plasmid VEGF/angiopoietin‐1 chimeric plasmid alone. 130 In another study, Wang et al concluded accelerated wound healing, as evidenced by increased angiogenesis and decreased inflammation, in a splinted excisional burn wound model, when the wound was treated with a hydrogel scaffold loaded with resveratrol and PEI/plasmid DNA encoding VEGF (Figure 5a,b ). 125 Despite these promising features, the high cationic charge density of PEI can result in cytotoxicity that originates from cell membrane disruption through electrostatic interactions.…”
Section: Gf Gene Deliverymentioning
confidence: 95%
“…In a rat full-thickness skin defect model, they demonstrated that these DGADSs led to significantly increased fibroblast infiltration, collagen deposition and neovascularization, accompanied by maturation of the vascular network. Hence, DGADSs show promise in facilitating the vascularization of functional tissue-engineered dermal substitutes for applications in wound repair [ 75 ].…”
Section: The Stages and Microenvironment Of The Healing Woundmentioning
confidence: 99%
“…According to the findings, the dual gene delivery method accelerates the healing of skin injuries by promoting angiogenesis and dermal tissue regeneration in a rat skin defect model. 40–42…”
Section: Gene-activated Dressing: Revolutions In the Treatment Of Ski...mentioning
confidence: 99%